Earthworks Rising : Mound Building in Native Literature and Arts - Allen, Chadwick (Book collections on Project MUSE., 2022)
"North America's Native peoples's ancient traditions of mound building--large-scale earthworks that remain visible today, particular at sites in Ohio and Mississippi, though evidence suggests that complex mound buildings once existed across much of today's United States. Allen seeks to place the meaning-making around these mounds through collaborations with contemporary Native artists, writers, and performers who confront settler colonial notions of these mounds as "mysterious." Through the lens of Native aesthetics, these mounds become "land-writing" that encode complex knowledges of human thinking and movement. In short, Allen's manuscript asks, "how might we better perceive and how might we better understand from Indigenous perspectives the remarkable accomplishments of North America's extensive and diverse mound-building cultures over a period of thousands of years?""--